Narrative Review on Ibrutinib: A New Targeted Therapy for Hematologic Cancers (Asian Journal of Pharmaceutics (AJP), 2025)
Ibrutinib is a potent and highly selective irreversible Bruton’s tyrosine kinase (BTK) inhibitor. It has transformedthe treatment of B-cell lymphomas, particularly mantle cell lymphoma and chronic lymphocytic leukemia (CLL).It is thought that BTK is essential for the survival and activation of healthy and cancerous B-cells. In recent years,an oral BTK inhibitor called ibrutinib has emerged as a ground-breaking treatment for hematological malignanciessuch as CLL. The viability of ibrutinib, though, could not end there. This drug has been identified to inhibit severaladditional kinases linked to solid cancers (epidermal growth factor receptor, human epidermal growth factorreceptor 2). Recent findings suggest that BTK may be a target for anti-solid tumor treatment. As a result, researchhas been done on ibrutinib, a BTK-inhibitor, as a potential treatment for solid tumors. This review provides anin-depth analysis of an intriguing medication, emphasizing its mechanism of action, metabolism, safety profile,clinical studies, authorized applications, and prospects in the future.